Towards sustainable micro and nano composites from fly ash and natural fibers for multifunctional applications - Pappu, Asokan; Kumar, Vijay (Elsevier, 2017)
Manufacturing of petroleum based synthetic materials, exploitation of timber products from forest reserves, improper management of industrial wastes and natural resources greatly persuade the environmental contaminations and global warming. To find viable solutions and reduce such alarming issues, innovative research work on recycling of unutilized materials such as fly ash and natural cellulosic polymers has been reported in this work to develop advanced sustainable hybrid micro/nano composites. In this study, the use of natural cellulosic sisal fibers with fly ash has enhanced the tensile properties and surface finish of composites. Fly ash particulates acted as fillers, additives, as well as surface-finishing medium and sisal fibers as reinforcing elements in achieving glossy finish sustainable composites. The developed composites have been found to be stronger than wood, plastics and have many opportunities for multifunctional applications.
Keywords: Sustainable micro and nano composites; Renewable resources; Mechanical properties; Timber and synthetic wood substitute; Waste particulates